2010
DOI: 10.1111/j.1748-8583.2010.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

HRM and strategic climates in hospitals: does the message come across at the ward level?

Abstract: This study examined how employees perceive intended strategic goals and HRM at the ward level, and if these perceptions generate the desired effects. The qualitative part of the research reveals that the hospital pursues two strategic goals (i.e. quality and safety). Analysis of the questionnaire data (N = 576 respondents; 59 wards) shows that both climate dimensions could be distinguished. Results showed that the perceived HR system does have a significant influence on both climate dimensions, suggesting that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(127 citation statements)
references
References 42 publications
2
117
0
8
Order By: Relevance
“…Although prior empirical research studied the positive impact of EI climates on employee attitudes and organizational effectiveness (e.g., Tesluk et al, 1999;Riordan et al, 2005), the study of climate strength in this relationship has been notably absent from the existing literature. Studies on organizational climate in the health care context in particular have neglected this critical distinction and have narrowly focused on climate level only (Veld et al, 2010). The present research addresses this gap and extends previous research on EI in decision"making in the health care context by studying the moderating role of EI climate strength in the EI climate level"outcome relationships (Parkes, et al, 2007;West and Dawson, 2012;.…”
Section: ( And(mentioning
confidence: 75%
“…Although prior empirical research studied the positive impact of EI climates on employee attitudes and organizational effectiveness (e.g., Tesluk et al, 1999;Riordan et al, 2005), the study of climate strength in this relationship has been notably absent from the existing literature. Studies on organizational climate in the health care context in particular have neglected this critical distinction and have narrowly focused on climate level only (Veld et al, 2010). The present research addresses this gap and extends previous research on EI in decision"making in the health care context by studying the moderating role of EI climate strength in the EI climate level"outcome relationships (Parkes, et al, 2007;West and Dawson, 2012;.…”
Section: ( And(mentioning
confidence: 75%
“…Quality of care is to mean the "degree to which health service for individuals and populations increase the likelihood of desired health outcomes(reduced pain, illness or morbidity and mortality) and are consistent with current professional knowledge in the sector" (9,(26)(27)(28).…”
Section: Resultsmentioning
confidence: 99%
“…Scholars (14,28) contend that in the HR field different types of outcomes are relevant and they make a distinction between three types: (1) financial outcomes (e.g. profits, sales, return on invested capital), (2) organizational outcomes (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Affected by HRM practices, procedures and social interactions with their peers, employees form collective perceptions on what the organization expects from them (Zhang et al, 2014). Previous research has indicated that the level of perceived expectations is linked with job performance (Jiwen Song et al, 2009) and that the level of different facets of climate impacts on employee outcomes, with employees found to comply with a group-level climate (Veld et al, 2010). Collective perceptions are thus important as they affect employee performance and ultimately organizational performance (Nishii and Wright, 2008).…”
Section: Introductionmentioning
confidence: 99%